Healthcare and culture : subjectivity in medical contexts - Freda, Maria Francesca; Picione, Raffaele De Luca (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
The book deals with current issues, pertinent every healthcare relationship. Changes in medicine as well as some constant aspects over time arise within a cultural ground and generate new questions and issues that are not only purely medical, but also bioethical, social, political, economic and psychological of course.On the one hand, changes in medicine generate new questions for society, on the other hand, the society poses new questions to the medicine, new challenges, and in some cases they can conflict with consolidated models and practices. Never the progress of Western medicine and its therapeutic practices have been as significant as in the last decades but the increase of specific competence and effectiveness of medical treatments are not linearly translated into an increase of consensus, dialogue and alliance between medicine and society. How does psychology take on a position of interlocutor towards medicine and its transformations? How does Cultural Psychology, Health Psychology, Clinical Psychology confront themselves with the processes of meaning making generated by medicine?The interest of the book is aimed to grasp the construction of processes of cultural, relational and subjective meaning in the dialogical encounter between medicine and society, between doctor and patient. The book intends to focus in particular on two specific plans: on the one hand, to present a reflection and analysis on contemporary medicine and its on-going transformations of the healthcare relationship; on the other hand, to present and discuss experiences of intervention and possible models of intervention addressed to healthcare and doctor-patient relationships during its crucial steps (consultation, formulation and communication of diagnosis, therapy, conclusion). The book's purposes are aimed to discuss crucial and current issues on the borders between medicine and psychology: consensus and sharing, decision-making and autonomy, subjectivity and narration, emotions and affectivity, medical semeiotics and cultural semiotics, training of physicians, and epistemological, theoretical and methodological issues.
Keywords: Transcultural medical care.; Medical care -- Cross-cultural studies.; Medical -- Health Care Delivery.; Personal and public health, health education.; Health systems and services.; elektronické knihy; electronic books